Chemotherapy-related cognitive impairment in older patients with cancer. Issue 4 (July 2016) - Loh, Kah Poh; Janelsins, Michelle C.; Mohile, Supriya G.; Holmes, Holly M.; Hsu, Tina; Inouye, Sharon K.; Karuturi, Meghan S.; Kimmick, Gretchen G.; Lichtman, Stuart M.; Magnuson, Allison; Whitehead, Mary I.; Wong, Melisa L.; et al.
Abstract: Chemotherapy-related cognitive impairment (CRCI) can occur during or after chemotherapy and represents a concern for many patients with cancer. Among older patients with cancer, in whom there is little clinical trial evidence examining side effects like CRCI, many unanswered questions remain regarding risk for and resulting adverse outcomes from CRCI. Given the rising incidence of cancer with age, CRCI is of particular concern for older patients with cancer who receive treatment. Therefore, research related to CRCI in older patients with cancers is a high priority. In this manuscript, we discuss current gaps in research highlighting the lack of clinical studies of CRCI in older adults, the complex mechanisms of CRCI, and the challenges in measuring cognitive impairment in older patients with cancer. Although we focus on CRCI, we also discuss cognitive impairment related to cancer itself and other treatment modalities. We highlight several research priorities to improve the study of CRCI in older patients with cancer.